A novel face mask design with improved properties for COVID-19 prevention. Issue 11 (June 2023) - Alby, Laine; Jayswal, Ajay; Morris, Sarah; McAtee, Will; Raghav, Vrishank; Adanur, Sabit
Novel cloth face masks to mitigate the spread of COVID-19 have been developed and tested for particle (0.1 μm in size) filtration efficiency, bacterial filtration efficiency, breathability, leakage, heart rate, and blood oxygen level, and then compared with the available N95 masks and surgical masks. It was found that this novel mask had better filtration efficiency than that of surgical masks and was very close to that of N95 masks. The breathability was also improved and was in the range of the designated levels for barrier face coverings. The flow visualization technique was utilized to study the leakage of the mask and it was found to have significantly lower leakage as compared to surgical masks. Heart rate and blood oxygen level tests were performed by wearing the mask during 10-minute walking sessions and it was found that wearing the mask did not adversely affect heart rate or blood oxygen levels or add any other strain on the wearer. It is believed that this novel face mask would reduce the spread of COVID-19 as well as provide an environmentally and economically conscious alternative to the N95 respirators for the public. The mask developed in this study can be washed, reused, and therefore worn for longer periods of time.